ANALISIS PENGARUH STOCK SPLIT, VARIABEL PASAR KEUANGAN DAN ECONOMIC VALUE ADDED (EVA) EMITEN TERHADAP RETURN SAHAM - Jenna Tania; Wisnu Mawardi; Danes Quirira Octavio (Diponegoro Journal of Management, 2023)
ABSTRACT This study examines stock splits, financial market variables, Economic Value Added (EVA) issuers which are likely to have an impact on stock returns. Financial market variables are: Earning per Share (EPS), Trading Volume Activity (TVA), market capitalization, and dividend yield. Data on 41 public companies that carried out corporate actions were collected based on financial reports, annual reports, and data output from bloomberg financial markets laboratory for a period of five years 2017- 2021. IBM SPSS Statistics 21 software is used to examine the relationship between variables: corporate actions, financial market variables, issuers' Economic Value Added (EVA) which are likely to have an impact on stock returns. The results show that most of the financial market variables have no effect on stock returns, except for Earning per Share which has a significant positive effect on stock returns. From this study, it was obtained that the variables used were only able to explain 21.6% of the factors that could affect stock returns. Thus, that there were still 78.4% of other aspects that could be further investigated. Based on the results of the discussion and conclusions, there are suggestions as follows: (1) Conduct research with a sample of issuers from certain sectors. (2) Adding other variables that are able to explain the effect on stock returns. (3) Future research should consider market risk factor as one of the variables.